Kepatuhan Memakai Masker dalam Upaya Memutus Rantai Penularan COVID-19 - Andi Siswanto (Jurnal Kesehatan Masyarakat Indonesia, 2022)
Background: COVID-19 is an infectious disease and quickly spreads from person to person through droplets that come out of an infected person when coughing, sneezing or talking. The use of masks is an effort to reduce the risk of transmission of COVID-19. Masks are suggested as a method of limiting community transmission by asymptomatic carriers or at least clinically undetected infected persons. In the COVID-19 pandemic, masks are one of the most effective steps in preventing the transmission of COVID-19, the use of masks is non-negotiable because droplets from symptomatic people or symptomatic people when sneezing, coughing droplets can be stuck in masks, masks are replaced once every 4 hours or wet or dirty. People who have been infected with COVID-19 can transmit the virus to other people through very close droplets because the droplets that come out of an infected person contain water particles with a diameter of > 5-10 µm. Objective: To see a picture of compliance using a mask. Methods: This research uses descriptive analytic study, with a sample of 162 people. Result: In using masks, people have high compliance during the pandemic. People are very obedient when leaving the house using masks by 99.38%, then changing masks every 4 hours is 64.20%. Conclusion: People are aware of the importance of personal health by always carrying a spare mask